PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK DENGAN MODEL PROBLEM BASED LEARNING BERBASIS HIGHER ORDER THINKING SKILLS - Ulfa Khairunisa; Zainal Azis; Metrilitna Br Sembiring (MES: Journal of Mathematics Education and Science, 2020)
This study aims to develop a Student Worksheet based on Higher Order Thinking Skills (HOTS) by using the Problem Based Learning model on the Sine and Cosine Rule learning material for class X high school students. The quality of the Student Worksheet refers to the validity of the Learning Implementation Plan and the Student Worksheet. Research and Development (RD) research type is used in this study. In this case, the development of the research refers to ADDIE development model, there are only 3 stages that are limited to the development stage only applied in the research development of Student Worksheet based on HOTS. The subjects in this study were high school student Worksheet Assessment sheet to measure validity. Based on validation that has been conducted, it was obtained that student worksheet based on HOTS developed with a Problem Based Learning model have valid criteria; Student worksheet based HOTS on the Sine and Cosine Rules learning material which was developed using Problem Based Learning model declared to have valid criteria with an average score 4,1 with a very predicate.